Investigating Social Exclusion in Late Prehistoric Italy: Preliminary Results of the ''IN or OUT'' Project (PHASE 1). (2014) - Saracino, Massimo; Zamboni, Lorenzo; Zanoni, Vera; Perego, Elisa
This report presents the preliminary results of the ''IN or OUT'' Project, a collaborative, interdisciplinary effort which aims to investigate social exclusion, marginality and the adoption of anomalous funerary rites in late prehistoric Italy. In particular, this contribution explores the incidence and meaning of practices of ritual marginalisation and funerary deviancy in the region of Veneto between the Bronze Age and the early Iron Age period.